San Francisco Sound. 1965-1967, rivoluzione in musica (De Musica, 2024)
The USA of the post-World War II era underwent a period of considerable economic expansion and widespread prosperity. The white middle class lives the American dream by relocating to tranquil suburbs where ownership of every type of household appliance is possible, and social conformity represents a distinctive status. In such a structured society, between the 1940s and 1950s, a counterculture emerges that is destined to sensibly alter the mindset of an entire generation. The Beat Generation, combined with the evolutions of jazz and the electric emergence of Rock and Roll, creates a cultural substrate from which a movement may arise. Primarily through music, a new generation of Americans will challenge the social structures of the United States. From 1965 in San Francisco, a genuine cultural revolution unfolds, with music as one of its most potent weapons, involving a significant portion of the youth population worldwide within a few short years. From the sidewalks of North Beach, young beatniks move to the apartments of Haight Ashbury, giving life to a community that gathers in venues where musical groups, originating in the Bay Area and destined for global fame, begin experimenting with a new form of art. This cultural vanguard, until 1967, succeeds in creating an inseparable bond between art and community. The intent of this article is to retrace the milestones, amid concerts, happenings, and festivals, that will characterize the cultural revolution between 1965 and 1967.